The Form of Resolution of Juvenile Delinquency in Indonesia - Ratih Mega Puspa Sari; Sivani Ardi Apritania (Jurnal Hukum, 2024)
The juvenile delinquency is an impact of a lack of understanding of the character possessed by a child who grows to maturity, apart from parental supervision and a lack of understanding of the rules and norms that apply in society so that deviations occur, in This is juvenile delinquency that often occurs, for example, bullying or brawls that occur until the occurrence of violence and the emergence of criminal violations. The purpose of this research is to analyze the factors of juvenile delinquency crimes in Indonesia, secondly to provide solutions for juvenile delinquency crimes in Indonesia. This study uses a descriptive research method with a normative juridical approach. The research data used is secondary data consisting of primary and secondary legal materials, with analysis of data obtained from research results in the form of data from Library research analyzed qualitatively. The results of this study, Solutions for Juvenile Delinquency Violations in Indonesia are the responsibility of all of us, through an approach in the field of Education, the learning curriculum is included as early as possible and can be started from grade VII education as the basis for understanding legal science, it is hoped that in the development of knowledge of juvenile delinquency law in Indonesia. can be overcome to make a better and more advanced generation, so that it becomes welfare, peace in accordance with the culture based on the values of Pancasila.